The illusion of accountability in the European Union - Gustavsson, Sverker, 1940-; Karlsson, Christer; Persson, Thomas (Routledge advances in European politics, 2009)
This book examines accountability in the European Union€from different perspectives and€considers whether EU citizens have real opportunities for holding decision-makers accountable.